Microsurgical Reconstruction with Vein Graft for Canalicular Duct Rupture: A Case Report - Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; Gede Wara Samsarga; Shita Diwyani Sudarsa; Astrinita Lestari Suyata; Chandra Wijaya Setiawan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Canalicular rupture is an injury to the lacrimal drainage system, commonly caused by sharp or blunt trauma to the periocular area due to violence, traffic accidents, sports, or falls. Inadequate management can lead to permanent epiphora, canalicular stenosis, and post-traumatic cosmetic disfigurement, necessitating appropriate surgical reconstruction. This study was conducted to evaluate the anatomical and functional outcomes of autologous vein grafting with silicone stent placement in the reconstruction of canalicular rupture. This study aimed to report our experience in canalicular duct rupture repair with silicone tube and dorsal metacarpal vein autograft. This study is a descriptive case series involving patients with canalicular rupture who underwent microsurgical reconstruction using autologous vein grafts. Patient data were collected prospectively from medical records and postoperative follow-up. Outcomes evaluated included anatomical success, functional success, and postoperative complications. After the canalicular repair, the patient showed improvement as indicated by reduced complaints of epiphora significantly. Canalicular duct rupture reconstruction with silicone tube and dorsal metacarpal vein autograft showed a good outcome in this case and successfully reduced epiphora of the patient.